2020
DOI: 10.3390/ijms21114063
|View full text |Cite
|
Sign up to set email alerts
|

Human Sperm Capacitation Involves the Regulation of the Tyr-Phosphorylation Level of the Anion Exchanger 1 (AE1)

Abstract: Bicarbonate uptake is one of the early steps of capacitation, but the identification of proteins regulating anion fluxes remains elusive. The aim of this study is to investigate the role of sperm solute carrier 4 (SLC4) A1 (spAE1) in the capacitation process. The expression, location, and tyrosine-phosphorylation (Tyr-P) level of spAE1 were assessed. Thereby, it was found that 4,4′-Diisothiocyano-2,2′-stilbenedisulfonic acid (DIDS), an SLC4 family channel blocker, inhibited capacitation in a dose-dependent man… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 43 publications
0
20
0
Order By: Relevance
“…CFTRs have been reported to be present in mammalian spermatozoa [ 118 , 119 , 120 , 121 ]. The role of CFTRs in sperm motility is not insignificant.…”
Section: Chloride Channelsmentioning
confidence: 99%
“…CFTRs have been reported to be present in mammalian spermatozoa [ 118 , 119 , 120 , 121 ]. The role of CFTRs in sperm motility is not insignificant.…”
Section: Chloride Channelsmentioning
confidence: 99%
“…The main sites of mammalian band 3 gene expression are erythroid cells and the kidney, but it is also expressed in the heart ( 132 ), and there is recent evidence that band 3 is involved in sperm capacitation ( 133 ). In the kidney, the band 3 gene is transcribed with an alternate promoter ( 134 , 135 ) resulting in an NH 2 terminus that is 65 residues shorter than red cell band 3 ( 136 ).…”
Section: Band 3 Structurementioning
confidence: 99%
“…phosphorylated tyrosine levels in the head of human sperm, which is critical for AR (Dona et al, 2020). Other researchers have also found that protein tyrosine phosphorylation in the sperm head region is relevant to AR (Dona et al, 2011;Andrisani et al, 2015).…”
Section: Discussionmentioning
confidence: 93%